Task Scheduling Framework of Multi-stage and Multi-strategy for Remote Sensing Satellites - Qunbin YUE; Xijie SHANG; Xiaoyong LIN; Wei FU (天地一体化信息网络)
With the deepening of the support of remote sensing satellites for all kinds of applications, the external environment faced by satellite mission planning system is complex and changeable, such as satellite orbit adjustment, sudden failure in orbit, random arrival of tasks, changes in imaging conditions, etc., and the randomness of emergency events is greatly improved.The traditional periodic centralized mission planning framework is gradually unable to meet the requirements of high timeliness and high response.By analyzed the types and changing rules of the external environment of the system, the task planning framework of segmented sub-strategy adjustment was designed, as well as the corresponding scheduling strategy and object state management mechanism, and the efficient response ability to emergency emergencies was realized.The technical framework was adopted in a remote satellite mission management and control system project and the corresponding software was developed.The actual operation results of the system showed that the technical framework of mission planning with segmented strategy proposed in this paper basically met the requirements of high adaptability and high response caused by dynamic changes of external environment, and greatly improved the automation degree and timeliness index of the system.